Synthesis and properties of a novel waterborne photosensitive resin for 3D printing - Qinghong Luo; Ting Zhang; Ruijie Xu; Hongping Xiang; Yanyan Cui; Zhiquan Li; Xiaoxuan Liu (eXPRESS Polymer Letters, 2023)
A series of novel waterborne photosensitive resins were prepared successfully with poly(propylene oxide) bis(2-aminopropyl ether), tricyclodecane dimethanol diacrylate, 2-isocyanatoethyl acrylate, and hydrochloric acid by Michael addition reaction. The results show that with the increasing double bonds content, the double bonds conversion increases from 78.7, 85.6 to 92.8% in the photopolymerization, respectively, and the gel content of the UV-cured film increases from 48.05, 69.10 to 83.28%. In addition, the glass transition temperature and tensile strength of the UV-cured film follow the same increasing trend. Moreover, the content of hydrochloride has a great influence on the hydrophilicity of the waterborne photosensitive resins. The studies indicated that as the hydrochloride content decreases, the surface water contact angle of the UV-cured film increases from 10.8, 22.9 to 51.5°, and water absorption decreases from 26.55, 16.20 to 11.06%, respectively. Moreover, the waterborne photosensitive resins exhibited a high printing accuracy together with a good effect of washing and are promising for 3D printing.